Implementasi Strategi Pembelajaran Snowball Throwing/Snowball pada Kelas VII Pondok Pesantren Modern Darul Hikmah TPI Medan - Arlina, Arlina; Aloken Marwahtah Br Ginting; Halamsyah Hamdani; Nevi Rizkia Yusuf (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This study aims to evaluate the improvement of Islamic jurisprudence learning by implementing the Snowball Throwing strategy in the seventh-grade class at Pondok Pesantren Modern Darul Hikmah TPI Medan. This method is intended to enhance the activity and engagement of students in discussions about Islamic jurisprudence. The research follows a qualitative descriptive approach involving observation, interviews, and document analysis from the indexed National Shinta journal. The process took place over one day at Pondok Pesantren Modern Darul Hikmah TPI Medan. The Snowball Throwing model is implemented to increase student engagement, foster an interactive learning environment, and improve students' learning outcomes in Islamic jurisprudence. Observations indicate that using the Snowball Throwing model resulted in active discussions that significantly impacted students' understanding of Islamic jurisprudence. Cognitive evaluations demonstrated a notable improvement in students' learning outcomes. Through Snowball Throwing-based learning, students were guided through structured steps, including objective delivery, group discussions, and evaluation of learning outcomes. The discussion outcomes showed an enhancement in students' performance from the initial assessment, albeit with variations between groups. The group with the highest score exhibited superior participation and understanding of the subject matter.